A measurement strategy for non-dispersive ultra-violet detection of formaldehyde in indoor air: Spectral analysis and interferent gases - Davenport, John; Hodgkinson, Jane; Saffell, John R.; Tatam, Ralph P. (Institute of Physics (IOP), 2016)
We have conducted an extensive review of published spectra in order to identify a region with potential for detection of formaldehyde in indoor air. 85 chemicals and chemical groups common to the indoor environment were identified, 32 of which had absorption spectra in the UV-vis region. Of these, 11 were found to overlap with the formaldehyde UV region. It was found that the region between 320 to 360 nm is relatively free from interference from indoor gases, with NO being the only major interferent. A method is proposed for a low resolution (3 nm) spectroscopic detection method, specifically targeted at formaldehyde absorption features at 327 nm with a reference at 334 nm. 32 ppb of NO was found to have a cross-sensitivity with equivalent magnitude to 100 ppb of formaldehyde. A second reference at 348 nm would reduce this cross-sensitivity.
Keywords: Formaldehyde; Gas sensing; Non-dispersive ultra-violet; NDUV; UV spectroscopy